Association of British Clinical Diabetologists (ABCD) and Diabetes UK joint position statement and recommendations on the use of sodium–glucose cotransporter inhibitors with insulin for treatment of type 1 diabetes (Updated October 2020). Issue 2 (26th November 2020) - Dashora, Umesh; Patel, Dipesh C.; Gregory, Robert; Winocour, Peter; Dhatariya, Ketan; Rowles, Susannah; Macklin, Andrew; Rayman, Gerry; Nagi, Dinesh; ,
Abstract: Dapagliflozin (SGLT‐2 inhibitor) and sotagliflozin (SGLT1/2 inhibitor) are two of the drugs of SGLT inhibitor class which have been recommended by the National Institute for Health and Care Excellence (NICE) in people with type 1 diabetes with BMI ≥27 kg/m 2 . Dapagliflozin is licensed in the UK for use in the NHS while sotagliflozin may be available in future. These and possibly other SGLT inhibitors may be increasingly used in people with type 1 diabetes as new licences are obtained. These drugs have the potential to improve glycaemic control in people with type 1 diabetes with the added benefit of weight loss, better control of blood pressure and more time in optimal glucose range. However, SGLT inhibitors are associated with a higher incidence of diabetic ketoacidosis without significant hyperglycaemia. The present ABCD/Diabetes UK joint updated position statement is to guide people with type 1 diabetes and clinicians using these drugs help mitigate this risk and other potential complications. Particularly, caution needs to be exercised in people who are at risk of diabetic ketoacidosis due to low calorie diets, illnesses, injuries, starvation, excessive exercise, excessive alcohol consumption and reduced insulin administration among other precipitating factors for diabetic ketoacidosis.